2021
DOI: 10.1177/10499091211055900
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of the Role of Palliative Care During the COVID-19 Pandemic: Perceptions and Experiences Among Critical Care Clinicians, Hospital Leaders, and Spiritual Care Providers

Abstract: Background Palliative care offers a unique skill set in response to challenges posed by the COVID-19 pandemic, with expertise in advance care planning, symptom management, family communication, end-of-life care, and bereavement. However, few studies have explored palliative care’s role during the pandemic and changes in perceptions and utilization of the specialty among health and spiritual care providers and hospital leaders. Objective To explore the utilization, perceptions, and understanding of palliative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Similarly, in Italy, Franchini et al (22) found that staff providing home palliative care services faced both patient-related and practice-related challenges, which required different communication methods and patient and family education, but staff felt a sense of satisfaction with their role during the first wave of the pandemic. In a hospital setting in the USA, Vesel et al (23) found that palliative care served as a bridge between providers, patients, and families and reinforced positive perceptions of palliative care.…”
Section: Discussion and Recommendations For Policy Practice And Publi...mentioning
confidence: 99%
“…Similarly, in Italy, Franchini et al (22) found that staff providing home palliative care services faced both patient-related and practice-related challenges, which required different communication methods and patient and family education, but staff felt a sense of satisfaction with their role during the first wave of the pandemic. In a hospital setting in the USA, Vesel et al (23) found that palliative care served as a bridge between providers, patients, and families and reinforced positive perceptions of palliative care.…”
Section: Discussion and Recommendations For Policy Practice And Publi...mentioning
confidence: 99%